2022
DOI: 10.1111/hepr.13747
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pemafibrate on primary biliary cholangitis with dyslipidemia

Abstract: Aim The purpose of this study was to examine the effect of pemafibrate (PEM) in primary biliary cholangitis (PBC) patients with dyslipidemia. Methods Patients who were diagnosed with PBC between June 2018 and December 31, 2020 were included in the study if they also had dyslipidemia and their alkaline phosphatase (ALP) or gamma‐glutamyl transferase (GGT) levels remained above the normal range despite taking 600 mg/day ursodeoxycholic acid (UDCA) for at least 6 months. Patients who were treated with UDCA alone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…Approximately 80% of asymptomatic patients have a higher risk of becoming symptomatic within ten years [ 6 ]. However, at baseline, only 20% are symptomatic [ 7 ]. The American Association for the Study of Liver Diseases Practice Guidance on PBC found no significant correlation between these symptoms and disease stage, although patients with more advanced disease stages generally have more symptoms [ 8 ] Among twenty (26.0%) out of the seventy-seven patients overall, twelve developed pruritus, two ascites, six esophageal varices, two hepatocellular carcinoma, and two jaundice, including patients who developed several symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 80% of asymptomatic patients have a higher risk of becoming symptomatic within ten years [ 6 ]. However, at baseline, only 20% are symptomatic [ 7 ]. The American Association for the Study of Liver Diseases Practice Guidance on PBC found no significant correlation between these symptoms and disease stage, although patients with more advanced disease stages generally have more symptoms [ 8 ] Among twenty (26.0%) out of the seventy-seven patients overall, twelve developed pruritus, two ascites, six esophageal varices, two hepatocellular carcinoma, and two jaundice, including patients who developed several symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Disturbances of the gut–liver axis are associated with various chronic liver diseases [ 10 ]. Epithelial barrier function and innate immunity both play crucial roles in the pathogenesis of PBC and its various forms of autoimmunity [ 7 ]. Having a defective epithelial barrier and increased intestinal permeability (IP) can promote an immunological response and elevate levels of circulating endotoxin [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, few reports have examined the effects of switching from conventional fibrates to pemafibrate. [13][14][15] In the package insert for bezafibrate in Japan, the incidence of adverse effects is listed as UDCA plus fibrates than with UDCA monotherapy. 16 Dohmen et al…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Yamaguchi et al showed that PEM add-on was as effective as BEZ add-on in PBC patients with dyslipidemia refractory to UDCA monotherapy. 5 They also showed that switching from BEZ to PEM normalized serum biliary enzyme activities in about 50% of patients who were an incomplete response to the combination of UDCA+BEZ. In some cases, biliary enzymes worsened after switching from BEZ to PEM, but it may be worth trying when UDCA+BEZ is not effective enough.…”
mentioning
confidence: 97%
“…Yamaguchi et al. demonstrated that effectiveness and safety of PEM for PBC 5 . However, there are several points to be clarified in the future.…”
mentioning
confidence: 99%